ANALISIS PENGARUH NILAI SUKUK, RATING SUKUK, DAN RISIKO SUKUK TERHADAP LAST YIELD SUKUK (Studi Kasus Perusahaan Konvensional non-bank yang Menerbitkan Sukuk di Indonesia Periode tahun 2008-2011) - Saraswati Almara, Dheni; Muharam, Harjum (Diponegoro Journal of Management, 2015)
This study aims to examine the factors that affect last yield sukuk. This study uses three independent  variables,  namely sukuk value, sukuk rating, and risk of sukuk. with the dependent variable is the last yield of sukuk.The sampling technique used was purposive sampling criteria (1) The Company listed its sukuk on the Indonesia Stock Exchange, (2) the company has sufficient data to do research. The data sample obtained was 19 companies. The analytical method used is a multivariate regression. The assumption of classical test and hypothesis test using t-statistic, testing the coefficient of determination  (R2),  and  the  F-statistic  to  test  the  effect  of  model  variables  together  with  a significance   level   of  5%.  This  study   also  includes   the  classic   assumption   normality   test, autocorrelation test, heteroscedasticity test, and multicollinearity test.Based  on  the  data  normality  test  results,  the  study  shows  that  the  data  are  normally distributed. Based on the test results with the classical assumption of multicollinearity test, autocorrelation  and heteroscedasticity  test did not find any data that deviate from the classical assumption. It shows that the data used in this study are qualified to use a multivariate regression model. From the analysis in this study shows sukuk value has a negative correlation coefficient and no significant effect on last yield sukuk, sukuk rating has a positive correlation coefficient and no significant effect on the last yield sukuk, and risk of sukuk has a negative correlation coefficient and significant effect on the last yield sukuk.